2015
DOI: 10.1517/13543776.2015.1045412
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins: improving the therapeutic response of analgesic drugs: a patent review

Abstract: We noticed that some patents are related to the complexation of opioids, NSAIDs, as well as natural products, in different types of CDs. The use of CDs creates the prospect of developing new therapeutic options for the most effective treatment of painful conditions, allowing a reduction of dosage of analgesic drugs and the occurrence of side effects. Thus, CDs can be an important tool to improve the efficacy and pharmacological profile of analgesic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…However, its poor solubility in water, short half-life and controversial effectiveness have all limited its use in chronic approaches, such as in models of chronic pain. On the other hand, cyclodextrins (CDs), such as βCD, have been a useful tool to improve several chemical and pharmacological properties of non-polar compounds as terpenes Oliveira et al, 2015). Thus, we complexed CT with βCD assessing whether it could improve the analgesic profile of CT, and also assessed its possible interactions with CNS areas related to pain control, aided with the docking study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its poor solubility in water, short half-life and controversial effectiveness have all limited its use in chronic approaches, such as in models of chronic pain. On the other hand, cyclodextrins (CDs), such as βCD, have been a useful tool to improve several chemical and pharmacological properties of non-polar compounds as terpenes Oliveira et al, 2015). Thus, we complexed CT with βCD assessing whether it could improve the analgesic profile of CT, and also assessed its possible interactions with CNS areas related to pain control, aided with the docking study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our research group has focused on the complexation of NP, mainly non-polar compounds such as terpenoids, with βCD (Nascimento et al, 2015;QuintansJúnior et al, 2013;Santos et al, 2015;Siqueira-Lima et al, 2014), and we have reported that this complexation was able to improve the effect of these substances mainly for FM or CMP approaches (Nascimento et al, 2014;. Moreover, preclinical and clinical evidence have demonstrated that the complexation in CDs is capable to improve pharmacological effect of analgesic and anti-inflammatory drugs Oliveira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the dose tested in our protocols is substantially smaller than the smallest dose of LEO described in the literature by Leite et al [ 20 ], because we used the 1 : 1 molar ratio of majority compound (geraniol: 154.24 g/mol) and β -CD (1135 g/mol), so we are using nominally around 10% of the dose used by Leite et al [ 20 ]. Therefore, this complex seems to present better analgesic effect using lower concentrations of active ingredient, with these benefits being already described for cyclodextrins [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 97%
“…Cyclodextrins are formed from the action of CD glycosyltransferase enzymes on starch, with the most important natural CDs being α, β, and γ [15]. Among the naturally occurring CDs, β-cyclodextrin (β-CD) is the one most commonly used for complexing drugs [14,[16][17][18][19] and natural products [19][20][21][22], with the aim of potentiating their pharmacological effects through increasing their stability and solubility, and making them into promising alternative treatment options.…”
Section: Introductionmentioning
confidence: 99%